Radiation Exposure of Workers and Volunteers in Shelters and Community Reception Centers in the Aftermath of a Nuclear Detonation. Issue 5 (May 2019) - Anderson, Jeri L.; Failla, Gregory; Finklea, Lauren R.; Charp, Paul; Ansari, Armin J.
Abstract : Abstract: After a nuclear detonation, workers and volunteers providing first aid, decontamination, and population monitoring in public shelters and community reception centers will potentially be exposed to radiation from people they are assisting who may be contaminated with radioactive fallout. A state-of-the-art computer-aided design program and radiation transport modeling software were used to estimate external radiation dose to workers in three different exposure scenarios: performing radiation surveys/decontamination, first aid, and triage duties. Calculated dose rates were highest for workers performing radiation surveys due to the relative proximity to the contaminated individual. Estimated cumulative doses were nontrivial but below the occupational dose limit established for normal operations by the Occupational Safety and Health Administration.